PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI RISIKO DAN FITUR LAYANAN TERHADAP MINAT MENGGUNAKAN E-WALLET DANA PADA GENERASI Z DI KOTA DENPASAR - Putri, Ida Ayu Kade Setia; Prawitasari, Putu Putri; Suryanata, I Gusti Ngurah Putra; Kustina, Ketut Tanti (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to evaluate the influence of perceived ease of use, perceived risk, and service features on the interest in using the DANA e-wallet among Generation Z in Denpasar. The advancement of technology in the 4.0 industrial era has encouraged the use of e-wallets as a primary payment method, especially among young people who prefer cashless transactions due to the convenience and flexibility offered. Using a quantitative approach with a sample of 100 respondents selected through purposive sampling, this research employed an online questionnaire to measure perceived ease of use, perceived risk, and service features as they relate to usage interest. Data analysis was conducted through multiple linear regression using SPSS. The findings show that all three independent variables have a positive and significant influence on the interest in using the DANA e-wallet. Perceived ease of use and service features have a substantial impact on influencing Generation Z’s interest, while perceived risk, although significant, has a lesser effect. This study's conclusions provide insights for developing e-wallet services that better align with Generation Z's preferences and suggest further research to include additional relevant variables and expand the geographical scope of study